Roads, Electricity, and Jobs : Evidence of Infrastructure Complementarity in Sub-Saharan Africa - Abbasi, Mansoureh; Lebrand, Mathilde Sylvie Maria; Mongoue, Arcady Bluette; Pongou, Roland; Zhang, Fan (World Bank, Washington, DC, 2022)
Evidence for road expansion and electrification as drivers of job creation is limited and mixed, with most studies having considered either one or the other, and only in isolation. This paper estimates the average and heterogeneous impacts of road and electricity investments and the interaction of the two on job creation over the past two decades in 27 countries of sub-Saharan Africa. Exploiting the exogenous location of ancestral ethnic homelands, a new instrumental variable is created for road accessibility, inspired by post-independence leaders' agenda of building roads to extend authority over the entire expanse of their country, and to promote nation building. Topography and lightning strikes—a key source of damage to electric lines and disruption of service—are used to instrument electricity supply. The paper finds positive and significant effects on employment from enhancing proximity to roads and to electric grids. Moreover, the interaction of the two enhances the effects, making them complementary investments. The impacts of both individual and bundled investments are positive, but with differences between men and women, workers of various ages, and countries at different stages of development. In urban areas, better access to roads and electricity promotes all types of employment. In rural areas, greater access induces a transition from low- to high-skilled occupations. These differential effects suggest that the structural transformation brought about by road and electricity expansion is primarily a rural phenomenon.